Perspectives in noninvasive imaging for chronic coronary syndromes. (15th October 2022) - Morrone, Doralisa; Gentile, Francesco; Aimo, Alberto; Cameli, Matteo; Barison, Andrea; Picoi, Maria Elena; Guglielmo, Marco; Villano, Angelo; DeVita, Antonio; Mandoli, Giulia Elena; Pastore, Maria Concetta; Barillà, Francesco; et al.
Abstract: Both the latest European guidelines on chronic coronary syndromes and the American guidelines on chest pain have underlined the importance of noninvasive imaging to select patients to be referred to invasive angiography. Nevertheless, although coronary stenosis has long been considered the main determinant of inducible ischemia and symptoms, growing evidence has demonstrated the importance of other underlying mechanisms (e.g., vasospasm, microvascular disease, energetic inefficiency). The search for a pathophysiology-driven treatment of these patients has therefore emerged as an important objective of multimodality imaging, integrating "anatomical" and "functional" information. We here provide an up-to-date guide for the choice and the interpretation of the currently available noninvasive anatomical and/or functional tests, focusing on emerging techniques (e.g., coronary flow velocity reserve, stress-cardiac magnetic resonance, hybrid imaging, functional-coronary computed tomography angiography, etc.), which could provide deeper pathophysiological insights to refine diagnostic and therapeutic pathways in the next future. Graphical abstract: CCTA allows a comprehensive assessment of CAD, while traditional functional imaging is aimed to assess myocardial ischemia. Since ischemia may be secondary either to epicardial coronary obstructive or to other conditions (e.g., vasospasm, microvascular dysfunction, energetic mismatch), the use of more modern techniques such as FFRCT, stress-CTP, CFVR, stress-CMR, and hybrid imaging may provide further information to tailor therapeutic choices to each patient. CAD: coronary atherosclerotic disease; CCTA: coronary computed tomography angiography; CFVR: coronary flow velocity reserve; CMR: cardiac magnetic resonance; CTP, computed tomography perfusion imaging; FFR, fractional flow reserve; MPI, myocardial perfusion imaging. Unlabelled Image Highlights: Both the latest European guidelines on chronic coronary syndromes and the American guidelines on chest pain have underlined the importance of noninvasive imaging. Other mechanisms than coronary stenosis (e.g., vasospasm, microvascular disease, energetic inefficiency) may underly inducible ischemia and symptoms. The search for a pathophysiology-driven treatment of these patients is an important objective of multimodality imaging, integrating "anatomical" and "functional" information.